Love, Desire and Transformation : From Ovid to Thomas Harris - Rato, Rui (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2017)
There is a connection between identity, desire and transformation. In an effort to touch upon the surface of this connection and its implications I effected a reading of Ovid‟s Metamorphoses and related it with Thomas Harris‟s The Hannibal Lecter Trilogy whose major topos is also metamorphosis. In both cases, the transformations are propelled by obsessive behaviour, by the character‟s passions which ultimately define them. Are we born with our identity or is it something we create and develop as we go along? Do our imaginations play a role in this endeavour at all? In my study of Ovid I found a link between one of his characters, Pygmalion, and Hannibal Lecter, particularly in their uniqueness and in their shared interest which is love. By bringing into focus the link between these two texts, I may be able to show, if nothing else, that some quests might very well be considered timeless, and that, if meaning is to be found, it must be made.